(untitled) (Community Based Medical Journal, 2013)
Forearm deformity secondary to giant solitary ulnar exostosis is rare. Here we described a rare presentation of symptomatic solitary giant exostosis involving the distal ulna resulting in ulnar bowing of the forearm in a five-years old girl. The tumour was completely resected and the defect was reconstructed with non vascularised fibular autograft. A wedge osteotomy was performed on the radius to correct the deformity. Nine months after surgery, the fibular autograft has fully incorporated and the deformity remains corrected with normal bone length and excellent hand function. There is no evidence of local recurrence. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13851 Community Based Medical Journal Vol.1(1) 2012 30-32